2016
DOI: 10.1152/ajplung.00050.2016
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic role of calcium-sensing receptors in the development and progression of pulmonary hypertension

Abstract: An increase in cytosolic free Ca(2+) concentration ([Ca(2+)]cyt) in pulmonary arterial smooth muscle cells (PASMC) is a major trigger for pulmonary vasoconstriction and a critical stimulation for PASMC proliferation and migration. Previously, we demonstrated that expression and function of calcium sensing receptors (CaSR) in PASMC from patients with idiopathic pulmonary arterial hypertension (IPAH) and animals with experimental pulmonary hypertension (PH) were greater than in PASMC from normal subjects and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 74 publications
4
88
0
Order By: Relevance
“…Our study also observed that the PLC inhibitor almost completely abolished the R-568-induced [Ca 2+ ] i increase. Compelling evidence has revealed that in colonic epithelial cells, CaSR stimulation by 5 mM [Ca 2+ ] o triggers DAG production [29], and in vascular smooth muscle cells, the upregulated TRPC6 mediated by CaSR is functionally sensitive to DAG [12]. DAG can directly increase TRPC6 activity and does not seem to affect the plasma membrane expression of TRPC6 [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also observed that the PLC inhibitor almost completely abolished the R-568-induced [Ca 2+ ] i increase. Compelling evidence has revealed that in colonic epithelial cells, CaSR stimulation by 5 mM [Ca 2+ ] o triggers DAG production [29], and in vascular smooth muscle cells, the upregulated TRPC6 mediated by CaSR is functionally sensitive to DAG [12]. DAG can directly increase TRPC6 activity and does not seem to affect the plasma membrane expression of TRPC6 [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about the Ca 2+ influx mechanism upon CaSR activation. Canonical transient receptor potential (TRPC) channels, nonselective cation channels, seem to be responsible for Ca 2+ entry induced by CaSR activation in some cell types, such as salivary ductal cells [11], vascular smooth muscle cells [12, 13], keratinocytes [14], MCF-7 breast cancer cells [15] and glomerular mesangial cells [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Transient receptor potential conical (TRPC) channels have been shown to function as both ROC and SOC in PASMC (Yu et al, 2003, 2004). We recently discovered that CaSR functionally interacts with TRPC6 channels in PASMC from IPAH patients and animals with experimental PH and may play important role in the development and progression of sustained pulmonary vasoconstriction and pulmonary vascular remodeling (Tang et al, 2016). As discussed earlier, extracellular Ca 2+ -induced increase in [Ca 2+ ] cyt is enhanced in IPAH-PASMC due to increased expression of CaSR (Yamamura et al, 2012).…”
Section: Casr Functionally Couples To Trpc Channels To Regulate [Ca2+mentioning
confidence: 99%
“…As discussed earlier, extracellular Ca 2+ -induced increase in [Ca 2+ ] cyt is enhanced in IPAH-PASMC due to increased expression of CaSR (Yamamura et al, 2012). Blockade of TRPC6 channels significantly inhibits extracellular Ca 2+ -induced increase in [Ca 2+ ] cyt in IPAH-PASMC (Tang et al, 2016). Overexpression of CaSR or TPRC6 in normal PASMC results in enhanced extracellular Ca 2+ -induced increase in [Ca 2+ ] cyt , however, overexpression of both CaSR and TRPC6 dramatically increases extracellular Ca 2+ -induced increase in [Ca 2+ ] cyt compared to either alone (Tang et al, 2016).…”
Section: Casr Functionally Couples To Trpc Channels To Regulate [Ca2+mentioning
confidence: 99%
See 1 more Smart Citation